Enhancement of proton conductivity of chitosan membrane enabled by sulfonated graphene oxide under both hydrated and anhydrous conditions - Liu, Y.; Wang, J.; Zhang, H.; Ma, C.; Liu, Jian; Cao, S.; Zhang, X. (Elsevier SA, 2014)
In this study, sulfonated graphene oxide (SGO) nanosheets with controllable sulfonic acid group loading are synthesized via the facile distillation- precipitation polymerization, and then incorporated into chitosan (CS) matrix to prepare nanohybrid membranes. The microstructure and physicochemical properties of the resulting membranes are extensively investigated. Compared with CS control and GO-filled membranes, SGO-filled membranes attain enhanced thermal and mechanical stabilities due to the strong electrostatic attractions between -SO3H of SGO and -NH2 of CS, which inhibit the mobility of CS chains. Additionally, the inhibited mobility reduces the area swellings of SGO-filled membranes, reinforcing their structural stabilities. The incorporation of SGO generates acid-base pairs along CS-SGO interface, which work as facile proton-hoping sites and thus construct continuous and wide proton transfer pathways, yielding enhanced proton conductivities under both hydrated and anhydrous conditions. Meanwhile, the conductivity can be elevated by increasing the sulfonic acid group loading and content of SGO. Particularly, incorporating 2.0% S4GO can afford the nanohybrid membrane a 122.5% increase in hydrated conductivity and a 90.7% increase in anhydrous conductivity when compared with CS control membrane. The superior conduction properties then offered a significant enhancement in H2/O2 cell performances to the nanohybrid membranes, guaranteeing them to be promising proton exchange membranes. © 2014 Elsevier B.V. All rights reserved.